Rethinking the Museum of Modern Art Kamakura - Kenji Watanabe (Docomomo Journal, 2022)
An exhibition about the works of Japanese Modern architect, Junzo Sakakura, entitled “Une architecture pour l’ homme Junzo Sakakura in Architectural Documents”, took place from 27 November 2013 to 23 February 2014. The exhibi- tion was organized by the National Archives of Modern Architecture, Agency for Cultural Affairs which was established in May 2012 for the first time in Japan. This exhibition could promote to rethink MoMA Kamakura as facing on dangerous situations to inherit as cultural heritage of Mod- ern Movement in Japan.